Pengaruh Model Cooperative Integrated Reading and Composition terhadap Keterampilan Membaca Pemahaman Siswa Kelas VIII SMP Perguruan Islam Ar-Risalah - Herdian, Feri; Ramadhan, Syahrul (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This article was written to describe the effect of Cooperative Integrated Reading and Composition (CIRC) Learning Model to comprehension reading skills the eighth grade students of SMP Perguruan Islam Ar-Risalah. This research was a quantitative research with descriptive method which used one group pretest and posttest design. The population in this research was 180 people however just one class become the sample in this research. The sample was determined with purposive sampling method and the choosen class was VIII Jizan Class with 30 students. The data of this research is score of comprehension reading skill test before and after using CIRC Learning Model. There were three things that obtained. First, the comprehension reading skill of the eighth grade students of SMP Perguruan Islam Ar-Risalah before using CIRC Learning Model (82,9), Second, the comprehension reading skill of the eight grade students of SMP Perguruan Islam Ar-Risalah after using CIRC Learning Model (87,2), and Third, based on the test with level 0,95 has obtained tcounted > ttable (2,62>1,69). It concluded that H1 was accepted. It was meant there were a significant effect from using CIRC Learning Model to the comprehension reading skills of the eighth grade students of SMP Perguruan Islam Ar-Risalah.